Perancangan User Interface Aplikasi Konsultasi Disabilitas dengan Metode Design Thinking untuk Mendukung Aksesibilitas dan Partisipasi Sosial Masyarakat - Febrina Larasati (Informasi Interaktif : Jurnal Informatika dan Teknologi Informasi, 2024)
In Indonesia, the paradigm towards people with disabilities is still considered a negative stigma for the majority of society and social discrimination unconsciously arises in society. To overcome this problem, it is necessary to empower people with disabilities so that they are no longer a group of social discrimination in society. The lack of information about disability, disability therapy, appropriate therapists, and the credibility check of therapists are also obstacles faced by people with disabilities and their relatives. Therefore, in an effort to support disability empowerment measures, a user interface (User Interface/User Experience) was designed for a disability consultation application called "disABLEd!".  With an application that summarizes all information about disability, it is hoped that it can help people with disabilities in obtaining information on therapy centers, therapists, and social support they need. The design method in this research is the design thinking method which is known to be user-centered. The results of user interface design testing show that user interface design using the design thinking method is proven to be suitable to meet the problems according to user needs.  Keywords: Disability, User Interface, Design Thinking.